Respiratory syncytial virus infection in children less than five years of age presenting as severe community-acquired pneumonia - Suganya, Mahalingam; Kalpana, Sivasambo; S, Elilarasi; B, Sarathbalaji (Indian Journal of Child Health, 2018)
Background: Respiratory syncytial virus (RSV) is a major cause of lower respiratory tract infection in young children in both the community and hospital setting. Ongoing surveillance of the clinical and molecular epidemiology of RSV genotypes is important to characterize prevalent and emerging genotypes that may have impact on vaccine development. Objective: To assess the epidemiology of RSV infection in children